2019
DOI: 10.3390/ijms20153818
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Clinical Validation of a Novel 4 Gene-Signature with Prognostic Utility in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is a high burden disease with several genes involved in tumor progression. The aim of the present study was to identify, generate and clinically validate a novel gene signature to improve prediction of overall survival (OS) to effectively manage colorectal cancer. We explored The Cancer Genome Atlas (TCGA), COAD and READ datasets (597 samples) from The Protein Atlas (TPA) database to extract a total of 595 candidate genes. In parallel, we identified 29 genes with perturbations in > 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…In brief, we screened 127 DEGs by comparing the gene expression profiles of primary tumors from metastatic patients with those from primary patients. Most previous studies focused on the differentially expressed regulators between tumor tissue and normal tissue (22)(23)(24). However, in the present study, we analyzed DEmiRNAs and DEGs between non-distant metastatic and distant metastatic COAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, we screened 127 DEGs by comparing the gene expression profiles of primary tumors from metastatic patients with those from primary patients. Most previous studies focused on the differentially expressed regulators between tumor tissue and normal tissue (22)(23)(24). However, in the present study, we analyzed DEmiRNAs and DEGs between non-distant metastatic and distant metastatic COAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the previous literature on the prognosis of CRC, 4 gene signatures [ 28 ], 9 gene signatures [ 7 ], hypoxia-related signature [ 29 ], autophagy score signature [ 30 , 31 ], somatic mutation signatures [ 32 ], metabolism-related signature [ 33 ], chemokine/chemokine receptor signature [ 34 ], and immune-related signature [ 35 ] had been constructed to predict the OS of CRC patients. However, these bioinformatic analyses only predict the prognosis of CRC patients at the RNA level, and there are few studies on the protein prognostic signature.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoembryonic antigen (CEA) was a recommended prognostic marker in CRC for tumor diagnosis and monitoring response to therapy (Campos-da-Paz et al, 2018 ). Ahluwalia et al ( 2019 ) identified a novel 4-gene prognostic signature that had clinical utility in colorectal cancer. However, there are few clinical studies about biomarkers and gene pathways which have no risk of recurrence and tumor survival time.…”
Section: Introductionmentioning
confidence: 99%